2021
DOI: 10.1007/s10072-020-04965-7
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Brain function during central fatigue induced by intermittent high-intensity cycling

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
3
1
Order By: Relevance
“…Central fatigue pertains to situations in which the capacity of the central nervous system to activate motoneurons restricts the expression of strength (Dalsgaard & Secher, 2007 ) and its duration after exercise can vary depending on several factors but usually lasts between minutes and hours postexercise (Carroll et al., 2017 ). Although central fatigue correlates with EEG changes (e.g., increased alpha power) (Ghorbani & Clark, 2021 ) the present study's recordings were not during a fatigue stage, possibly explaining the negative results. Exercise‐induced changes in mood (Roeh et al., 2020 ; Schoenfeld & Swanson, 2021 ), linked to increased cortical excitation, are another significant factor.…”
Section: Discussioncontrasting
confidence: 71%
“…Central fatigue pertains to situations in which the capacity of the central nervous system to activate motoneurons restricts the expression of strength (Dalsgaard & Secher, 2007 ) and its duration after exercise can vary depending on several factors but usually lasts between minutes and hours postexercise (Carroll et al., 2017 ). Although central fatigue correlates with EEG changes (e.g., increased alpha power) (Ghorbani & Clark, 2021 ) the present study's recordings were not during a fatigue stage, possibly explaining the negative results. Exercise‐induced changes in mood (Roeh et al., 2020 ; Schoenfeld & Swanson, 2021 ), linked to increased cortical excitation, are another significant factor.…”
Section: Discussioncontrasting
confidence: 71%
“…While few studies investigated cortical activation during stationary cardiovascular exercise and majorly reported broadband changes in brain activity independent from frequency band and brain region (Ghorbani and Clark 2021 ; Robertson and Marino 2015 ), there is a lack of studies investigating the activation of the human brain during continuous open-skill exercise. Nevertheless, the variable environment in open-skill exercise may elicit continuous behavioral adaptations which require increased attentional demands (Wang et al 2013a ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported by several studies that EEG θ activity increases as the need for cognition and mental load does [ 31 , 32 ]. Many studies have also confirmed the presence of central fatigue-related changes in the θ band [ 33 , 34 ]. Furthermore, the slow-wave component of the brain increases after high-intensity exercise [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 97%